Pengaruh Penambahan Urea pada Mediad dan Pemanasan terhadap Produksi Biogas - Kadek Mila Adiani; Ida Bagus Putu Gunadnya; Yohanes Setiyo (Jurnal BETA (Biosistem dan Teknik Pertanian), 2020)
Biogas is one of the energy sources originating from livestock waste, besides being environmentally friendly (renewable energy), it can also be used for sustainable energy. Biogas is a mixture of gases resulting from an anaerobic fermentation process from livestock manure (cow). The purpose of this study was to determine the effect of adding various urea concentrations and heating in deep biogas production. This study applied a completely randomized design (RAL) with two treatment factors: heating (heating and without heating) and urea concentration (2%, 4%, 6%, 8%). Observations carried out in the form of measuring the temperature of biogas media, gas volume, CO2, the volume of methane gas, and the time of biogas formation. Variant analysis showed that the heating interaction and urea concentration showed a significant effect (P <0.05) on the measurement of biogas media temperature, gas volume, CO2, methane volume, and biogas formation time. The results showed that the combination of heating treatment with 8% urea concentration was the best treatment in producing biogas with the characteristics of gas volume of 16.67 ml, CO2 content of 0.08%, methane volume of 15.49 ml, with the time of biogas formation which is on the day 10.